The Feasibility of Establishing a Manufacturing Company in Quezon City Which Produces Corn/Soy Meal to Reduce Malnutrition Among Children in The Philippines - Egerton Manetho, Metuge Kogeh; Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2022)
This feasibility study was done to determine the feasibility of establishing a manufacturing company in Quezon City which produces Corn/Soymeal to reduce malnutrition among children in the Philippines. In this feasibility study, both quantitative and qualitative methodology was used to carry out the feasibility studies. In the quantitative methodology, statistical data was gathered from the Department of Education (DepED), the World Food Programme, and other important agencies, both public and private, as well as international organizations whereas for the qualitative methodology, interviews were conducted at the DepEd to get more information about the market, industry. The research paradigm followed an interpretive school of thought. The variables used in this research were independent and dependent variables. Some of the dependent variables were the data gotten from interviews conducted at DepED. The independent variables were the DepED employees and the World Food Programme because the findings of the feasibility studies depended on the data they provided. It was discovered that there is a considerable market opportunity for Corn/Soy meal in Metro Manila and that the utilization of recent and highly advanced types of machinery equipment will give the business a huge potential for success and increased productivity.